GNAL mutation in isolated laryngeal dystonia. Issue 5 (1st February 2016) - Putzel, Gregory G.; Fuchs, Tania; Battistella, Giovanni; Rubien‐Thomas, Estee; Frucht, Steven J.; Blitzer, Andrew; Ozelius, Laurie J.; Simonyan, Kristina
ABSTRACT: Background: Up to 12% of patients with laryngeal dystonia report a familial history of dystonia, pointing to involvement of genetic factors. However, its genetic causes remain unknown. Method: Using Sanger sequencing, we screened 57 patients with isolated laryngeal dystonia for mutations in known dystonia genes TOR1A (DYT1), THAP1 (DYT6), TUBB4A (DYT4), and GNAL (DYT25). Using functional MRI, we explored the influence of the identified mutation on brain activation during symptomatic task production. Results: We identified 1 patient with laryngeal dystonia who was a GNAL mutation carrier. When compared with 26 patients without known mutations, the GNAL carrier had increased activity in the fronto‐parietal cortex and decreased activity in the cerebellum. Conclusions: Our data show that GNAL mutation may represent one of the rare causative genetic factors of isolated laryngeal dystonia. Exploratory evidence of distinct neural abnormalities in the GNAL carrier may suggest the presence of divergent pathophysiological cascades underlying this disorder. © 2016 International Parkinson and Movement Disorder Society